2007
DOI: 10.2478/cmam-2007-0022
|View full text |Cite
|
Sign up to set email alerts
|

Sharp Expressions for the Stabilization Parameters in Symmetric Interior-penalty Discontinuous Galerkin Finite Element Approximations of Fourth-order Elliptic Problems

Abstract: -In this paper, we derive explicit expressions for the penalty parameters appearing in symmetric and semi-symmetric interior-penalty discontinuous Galerkin finite element method (DGFEM) for fourth-order elliptic problems. We demonstrate the sharpness of the theoretically predicted penalty parameter values through numerical experiments.2000 Mathematics Subject Classification: 65N12, 65N30.Keywords: discontinuous Galerkin finite element method, stabilized finite element methods, error bounds, stability and conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 16 publications
0
12
0
1
Order By: Relevance
“…An explicit expression for the penalty parameter α 0 in the interior-penalty discontinuous Galerkin finite element approximation of a second-order elliptic problem was proposed by Shabhazi [55] for meshes consisting of simplicial elements. The explicit dependence of the coercivity constant C 0 on the polynomial degree and the angles of the triangular/quadrilateral mesh elements was derived by Epshteyn and Rivière [33]; Mozolevski and Bösing [46] derived explicit expressions for penalty parameters in symmetric interior-penalty discontinuous Galerkin approximations of fourth-order elliptic problems on meshes consisting of parallelepipeds. 4.…”
Section: Discontinuous Galerkin Finite Element Approximationmentioning
confidence: 99%
“…An explicit expression for the penalty parameter α 0 in the interior-penalty discontinuous Galerkin finite element approximation of a second-order elliptic problem was proposed by Shabhazi [55] for meshes consisting of simplicial elements. The explicit dependence of the coercivity constant C 0 on the polynomial degree and the angles of the triangular/quadrilateral mesh elements was derived by Epshteyn and Rivière [33]; Mozolevski and Bösing [46] derived explicit expressions for penalty parameters in symmetric interior-penalty discontinuous Galerkin approximations of fourth-order elliptic problems on meshes consisting of parallelepipeds. 4.…”
Section: Discontinuous Galerkin Finite Element Approximationmentioning
confidence: 99%
“…In particular, they showed that the parameter depends on the smallest cot θ over all angles of the triangle in 2D or over all dihedral angles in the tetrahedron in 3D. For further study on the penalty problem, we refer the readers to [5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 98%
“…It is noted that some dimensionless penalty parameters presented in symmetric fully discontinuous IP methods and C 0 IP methods must be chosen large enough to guarantee stability, which can not be precisely quantified a priori, yielding some difficulty in practical applications. To resolve this problem, several explicit expressions for penalty parameters in symmetric IP methods on parallelepiped partitions were derived in [38]. Through introducing lifting operators, Wells and Dung proposed in [45] a C 0 DG (CDG) method whose penalty coefficients can be precisely quantified a priori.…”
Section: Introductionmentioning
confidence: 99%